Predictors of negative symptoms in the chronic phase of schizophrenia: A cross-sectional study. (April 2018) - Fujimaki, Koichiro; Toki, Shigeru; Yamashita, Hidehisa; Oyamada, Takahiro; Yamawaki, Shigeto
Abstract: This study was designed to investigate the relationship between negative symptoms and key indicators for long-term hospital stays among inpatients with schizophrenia. A further aim was to elucidate the clinical determinants of negative symptoms. The following were used as index factors: age, duration of illness, duration of hospitalization, age at onset, years of education, smoking status, body mass index, concentrations of serum triglycerides, total cholesterol, uric acid, QTc interval duration from electrocardiography, dose equivalents of antipsychotic and anticholinergic agents, neurocognitive function, drug-induced extrapyramidal symptoms, involuntary movements, and psychiatric symptoms. Spearman's rank correlation coefficients were calculated and regression analyses were performed to examine associations between these factors and negative symptoms. Positive symptoms correlated positively with negative symptoms as rated on the Brief Psychiatric Rating Scale. Age at onset correlated negatively with negative symptoms. Multiple regression analysis showed that dose equivalents of atypical antipsychotics and positive symptoms predicted negative symptoms. Increasing our understanding of these predictors as key indicators of the severity of negative symptoms may aid in the reconsideration of therapeutic programs for chronic schizophrenia. Highlights: Positive symptoms correlated positively with negative symptoms. Age at onset correlated negatively with negative symptoms. Positive symptoms predicted negative symptoms in multiple regression analysis. Dose equivalents of atypical antipsychotics predicted negative symptoms. These predictors may aid in the reconsideration of therapeutic programs.